Meningkatkan Kreativitas Generasi Muda Pematang Siantar Dengan Workshop Menjadi Konten Kreator Di Media Sosial - Hengki Mangiring Parulian Simarmata; Doris Yolanda Saragih; Henry Dunan Pardede; Poltak Pardamean Simarmata (Universitas Maritim AMNI Semarang, 2023)
Content creator training conducted by the Indonesian Business Polytechnic in collaboration with the Simarmata Young Generation to increase young people's creativity. This activity aims to increase young people's knowledge of using social media to get various benefits. Activities are carried out in workshops accompanied by practices using Instagram and TikTok media as content media. Seventy youth participants from Pematang Siantar attended the action. The training continued enthusiastically because the speaker is an activist content creator on YouTube, TikTok, and Instagram. After the activity, an activity survey showed that 98% of the participants were very interested in the material presented and gained new knowledge about using social media for more positive things.